Morphokinetic Analyses of Fishing Cat–Domestic Cat Interspecies Somatic Cell Nuclear Transfer Embryos Through A Time-Lapse System - Hai-Jun Liu; Serena Jocelyn Wai Yin Oh; Nicole Liling Tay; Christina Yingyan Lim; Chia-Da Hsu; Delia Hwee Hoon Chua; Winnie Koon Lay Teo; Yuin-Han Loh; Soon Chye Ng (Animals)
A time-lapse live embryo monitoring system provides a powerful approach to recording dynamic developmental events of cultured embryos in detail. By obtaining continuous short-interval images, blastocyst formation can be predicted and embryos can be selected. The objective of this study was to investigate the morphokinetic parameters of fishing cat–domestic cat interspecies somatic cell nuclear transfer (iSCNT) embryos from one-cell to blastocyst stages, and in particular, the cleavage patterns of the first division in iSCNT and IVF embryos, as these play a central role in euploidy. Domestic cat in vitro fertilization (IVF) embryos were set up as controls. The results show that morula and blastocyst development rates were significantly lower in the iSCNT embryos compared to their IVF counterparts. All earlier time points of embryonic development before the onset of blastulation in the iSCNT embryos were significantly delayed when compared with their IVF counterparts. In iSCNT, normal embryos (defined as those that developed to the blastocyst stage) took a longer time to reach the morula stage, and these morulas were more likely to undergo compaction, compared to their arrested embryo counterparts. Direct cleavage in the first division is a morphological aberration, and was seen with greater prevalence in iSCNT embryos than control IVF embryos; these aberrant embryos displayed a significantly lower blastocyst development rate than embryos that had undergone normal cleavage. In conclusion, the morphokinetic parameters of fishing cat–domestic cat iSCNT embryos at early stages could be used to predict their potential for development to the blastocyst stage. A time-lapse imaging system is potentially a powerful tool for selecting early embryos with developmental potential for transfer, and hence, for improving feline iSCNT efficiency.